Role of Internet of Things in the Smart Grid Technology - Al-Ali, Abdulrahman (2015)
The Internet of Things (IoT) has recently emerged as enabling technology for the smart gird, smart health, smart transportation, and smart environment as well as for smart cities. The major smart grid devices are smart home appliances, distributed renewable energy resources and power substations. The seven domains existing smart grid conceptual model was developed without the IoT concept in mind. As the smart grid evolved, many attempts started to introduce the IoT as enabling technology to the grid. Each device in the grid can be considered as an object. Utilizing the concept of IoT, each device can have a unique IP address that can upload its status and download control commands via the Internet. This paper proposes a conceptual model for the smart grid within the Internet of Things context. The proposed model is based on IPV6 as the backbone of the smart grid communications layer.